A comparison of job descriptions for nurse practitioners working in out‐of‐hours primary care services: implications for workforce planning, patients and nursing. Issue 5 (2nd December 2016) - Teare, Jean; Horne, Maria; Clements, Gill; Mohammed, Mohammed A
Abstract : Aims and objectives: To compare and contrast job descriptions for nursing roles in out‐of‐hours services to obtain a general understanding of what is required for a nurse working in this job. Background: Out‐of‐hours services provide nursing services to patients either through telephone or face‐to‐face contact in care centres. Many of these services are newly created giving job opportunities to nurses working in this area. It is vital that nurses know what their role entails but also that patients and other professionals know how out‐of‐hours nurses function in terms of competence and clinical role. Design: Content analysis of out‐of‐hours job descriptions. Method: Content analysis of a convenience sample of 16 job descriptions of out‐of‐hours nurses from five out‐of‐hours care providers across England was undertaken. The findings were narratively synthesised, supported by tabulation. Results: Key role descriptors were examined in terms of job titles, managerial skills, clinical skills, professional qualifications and previous experience. Content analysis of each out‐of‐hours job description revealed a lack of consensus in clinical competence and skills required related to job title although there were many similarities in skills across all the roles. Conclusion: This study highlights key differences and some similarities between roles and job titles in out‐of‐hours nursing but requires a larger study to inform workforce planning. Relevance to clinical practice: Out‐of‐hours nursing is a developing area of practice which requires clarity to ensure patient safety and quality care.